State Financial Management According to Al-Mawardi and Al-Ghazali - Nahlah Nahlah; Rahman Ambo Masse; Muslimin Kara; Ridwan Markarma (Sharia and Law Faculty, 2022)
This research aims to study the economic thinking of Muslim scholars who lived during the Abbasid dynasty, namely Al-Mawardi, and Al-Ghazali. Where does the state get financial resources according to Al-Mawardi, and what is the theory of money and markets from Al-Ghazali's perspective? The research method is qualitative with a literature study approach that originates from international journals, national journals, websites, and books by Al-Mawardi and Al-Ghazali. The results showed that according to Al-Mawardi, the sources of state finance were obtained through the collection of zakat, Khaimah, fa'i, jizyah, kharaj, public ownership, taxes, and debt. Furthermore, Al-Ghazali's perspective on money is as a medium of exchange in trade. It has